CRUSADE Bleeding Score as a Predictor for the Risk of Bleeding Events in Patients with Acute Coronary Syndrome: A Prospective Study from Tamil Nadu - Aneena Suresh (Journal of Global Pharma Technology, 2020)
Background: The CRUSADE bleeding risk score is an accurate and robust risk-stratification tool for predicting hemorrhagic complications in patients with Acute Coronary Syndrome (ACS). However, studies assessing and validating this score especially within Indian population are scarce to almost non-existent. Objective: To evaluate the Crusade Bleeding Score in predicting the risk of bleeding events in patients with acute coronary syndrome. Methods: This cross-sectional study was conducted at a secondary care hospital in Tamil Nadu, India. A total of 72 patients with ACS on treatment with anti-thrombotics that fulfilled the inclusion criteria of the study were prospectively recruited. The patient’s demographic data along with their past medical history pertinent to the study was collected and the scores for each patient was calculated. Results: Significant major bleeding was found among considerably older, female patients, diabetic and hypertensive patients, as also among patients having lower GFR values. Five patients classified under the Very High-Risk Category of the CRUSADE bleeding score further went on to develop hemorrhagic complications thereby validating the score among the study population. Conclusion: The CRUSADE bleeding score was found to be an accurate predictor of bleeding events within our study population with good validity. We further recommend the suitable use of the CRUSADE bleeding risk score in clinical practice as there is a need for stronger evidence to support the use of risk stratification systems to optimize therapy and improve patient outcomes in India.